Enhancing Student Vocabulary Proficiency through the Effective Implementation of Multimodal Approaches - Nadia, Riya (CV. PUSDIKRA MITRA JAYA, 2023)
Language barriers in educational settings can hinder effective communication and impede language learning, particularly when students cannot speak English fluently, and teachers struggle to understand the students' native languages. This study explores the efficacy of multimodal approaches to overcome language barriers and enhance vocabulary learning in a school with limited English language instruction. The identified problem encompasses students lacking vocabulary and English speaking abilities due to the language barrier and insufficient language learning opportunities. To address these challenges, a solution involving multimodal techniques through pictures, bingo games, mix-and-match games, PowerPoint presentations, and Google Translate was implemented. The research adopts a Class Action Research (CAR) methodology, allowing collaborative efforts with participants to implement multimodal strategies effectively. Observations and assessments were conducted to measure changes in students' vocabulary proficiency and language skills after the intervention. Additionally, qualitative data was gathered through interviews with ten students from the highest rank to gain insights into their experiences with multimodal approaches.